The versatile defender: exploring the multifaceted role of p62 in intracellular bacterial infection - Zhou, Yuhao; Hua, Shucheng; Song, Lei (Frontiers in Cellular and Infection Microbiology, 2023)
As a highly conserved, multi-domain, and multi-functional protein, p62/SQSTM1 participates in a variety of essential cellular activities especially selective autophagy. Emerging evidence has proved that p62 is involved in host cell’s elimination of various strains of intracellular bacteria mainly through xenophagy, a kind of selective autophagy specifically recognizing and eliminating intracellular pathogenic microbes. Based on published articles, this review summarizes roles of p62 in intracellular bacterial infection, including direct and indirect, antibacterial and infection-promoting, xenophagy-dependent and xenophagy-independent aspect. Potential synthetic drugs targeting p62-mediated xenophagy and unveiled myteries about roles of p62 in bacterial infection are also discussed.